Chemical vs. Enzymatic Refining to Produce Peanut Oil for Edible Use or to Obtain a Sustainable and Cost-Effective Protector for Stored Grains against Sitophilus zeamais (Coleoptera: Curculionidae) - Monica Macaluso; Priscilla Farina; Linda Rossi; Alessandro Bianchi; Francesca Venturi; Rodrigo Daniel Chiriboga Ortega; Stefano Bedini; Barbara Conti; Luca Guidi; Angela Zinnai (Foods, 2022)
Among the various existing techniques, enzymatic degumming represents a process that is establishing itself as a valid alternative to the more classic chemical processes. Moreover, vegetable oils of various origins have been gaining more consideration as sustainable and affordable protectants for cereals and pulses against the attack of several insect pests. Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae) is one of the key pests of cereal crops in the field and in stored and processed cereal products. Based on these highlighted issues, the overall aim of this research was twofold: (i) firstly, the effectiveness of the enzymatic degumming process was evaluated through the use of three different enzymes in order to verify the possible industrial application within the SALOV company as an alternative to the conventional chemical process; (ii) in a second phase, the possible use of the innovative refined oils was explored for sustainable stored grain protection towards S. zeamais. The results obtained confirm the strong possibility of applying the enzymatic process, which is innovative and, in a chemical way, more sustainable than the classical one. Regarding the toxicity towards S. zeamais, the crude peanut oil and the chemically refined peanut oil had lower LC50 values (1.836 and 1.372 g kg−1, respectively) than the oils rectified through enzymatic degumming (LC50 from 2.453 to 4.076 g kg−1), and, therefore, they can be suggested as sustainable stored grain protectants.